S‐acylation anchors remorin proteins to the plasma membrane but does not primarily determine their localization in membrane microdomains. Issue 3 (4th June 2014) - Konrad, Sebastian S. A.; Popp, Claudia; Stratil, Thomas F.; Jarsch, Iris K.; Thallmair, Veronika; Folgmann, Jessica; Marín, Macarena; Ott, Thomas
Summary: Remorins are well‐established marker proteins for plasma membrane microdomains. They specifically localize to the inner membrane leaflet despite an overall hydrophilic amino acid composition. Here, we determined amino acids and post‐translational lipidations that are required for membrane association of remorin proteins. We used a combination of cell biological and biochemical approaches to localize remorin proteins and truncated variants of those in living cells and determined S‐acylation on defined residues in these proteins. S‐acylation of cysteine residues in a C‐terminal hydrophobic core contributes to membrane association of most remorin proteins. While S‐acylation patterns differ between members of this multi‐gene family, initial membrane association is mediated by protein–protein or protein–lipid interactions. However, S‐acylation is not a key determinant for the localization of remorins in membrane microdomains. Although remorins bind via a conserved mechanism to the plasma membrane, other membrane‐resident proteins may be involved in the recruitment of remorins into membrane domains. S‐acylation probably occurs after an initial targeting of the proteins to the plasma membrane and locks remorins in this compartment. As S‐acylation is a reversible post‐translational modification, stimulus‐dependent intracellular trafficking of these proteins can be envisioned.